DEPĂŞIREA CONSERVATORISMULUI REPREZENTAŢIONAL FACTORUL PRACTICI SOCIALE - USM ADMIN (Moldova State University, 2009)
The resistance that appears during the transformation of social representations can ultimately be broken. This becomes a reality every time certain social practices, which are widely spread, visible, active, profitable, recurrent, extremely frequent, and easily recognizable and in full conformity with the new imperatives of the time, appear. In such an important context, the change of representation becomes the consequence of a behavioral submission, it becomes the consequence of certain circumstances that make us find a way to establish a consistent universe, sometimes inaccessible as a result of a contradiction between fact and reason.